2004
DOI: 10.1590/s0103-84782004000500031
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay for the detection of IgG antibodies against Babesia equi in horses

Abstract: A crude antigenic preparation of Babesia equi was used to develop and establish the suitability of an enzyme-linked immunosorbent assay (ELISA) for the detection of parasite carriers. Optimal dilutions of the antigen, using positive and negative reference sera, were determined by checkboard titrations. The specificity and sensitivity of the ELISA were 100 %. A total of 90 serum samples were taken from horses from the Northeast region of São Paulo State and examined for diagnosis of equine B. equi infection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
4
18
0
6
Order By: Relevance
“…Also, an ELISA test was performed as reported elsewhere (BALDANI et al, 2004) with an antigen concentration of 10 µg.mL -1 and a serum dilution of 1:100. The immunological activity of each serum was calculated by determining the sample-to-positive serum ratio (S/P), considering positive and negative sera as reference.…”
Section: Theileria Equi Serologymentioning
confidence: 99%
“…Also, an ELISA test was performed as reported elsewhere (BALDANI et al, 2004) with an antigen concentration of 10 µg.mL -1 and a serum dilution of 1:100. The immunological activity of each serum was calculated by determining the sample-to-positive serum ratio (S/P), considering positive and negative sera as reference.…”
Section: Theileria Equi Serologymentioning
confidence: 99%
“…Serological studies concerning infection by B. caballi and T. equi have shown that these two agents are widely distributed in Brazil, with herd prevalence ranging from 1.4 to 100% (BARBOSA et al, 1995;BITTENCOURT et al, 1997;KERBER et al, 1999;RIBEIRO et al, 1999;XUAN et al, 2001;BOTTEON et al, 2002;BALDANI et al, 2004;2007;COSTA PEREIRA et al, 2005;HEIM et al, 2007). These values have been shown to be affected by climatic conditions and farm management.…”
Section: Introductionmentioning
confidence: 99%
“…Heuchert et al (1999) tested 752 serum samples from the State of São Paulo by IFAT and CFT and reported prevalence rates of 29.6% and 17.6%, respectively. Moreover, serum samples from 90 horses of the same region of the present study were tested by ELISA and the prevalence of B. equi found was 75% (Baldani et al 2004). The frequency of equine piroplasmosis recorded in this study is significantly higher than that recorded by Heuchert et al (1999).…”
Section: Resul Resul Resul Resul Results and Discus Ts And Discus Ts mentioning
confidence: 87%
“…Therefore, the advantages and disadvantages of each test should be considered at the moment of choice of the best test for the diagnosis of equine piroplasmosis. It should be mentioned that the standardization of the ELISA was performed in a previous study, which demonstrated that the specificity and sensitivity of the test using a crude antigenic preparation of B. equi was 100% (Baldani et al 2004), with the advantage of using very low concentration of the antigen (10µg/mL) when compared to those reported by Kumar et al (2003), which varied between 370µg/mL and 500µg/mL. The IFAT, on the other hand, showed cross-reactions with B. caballi reference sera, although titers were not very high (≤1:80).…”
Section: Resul Resul Resul Resul Results and Discus Ts And Discus Ts mentioning
confidence: 99%
See 1 more Smart Citation